Cardiovascular adverse events associated with oral antineoplastic therapy - Silva,Jacqueline Mota da (2018)
ABSTRACT Objective: To identify in the literature the cardiovascular adverse events resulting from oral antineoplastic therapy. Method: Integrative review of the literature through the SCOPUS, Scientific Electronic Library Online (SciELO), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. The antineoplastic, cardiotoxicity, cardiovascular system and adverse reaction descriptors were used in Portuguese, English and Spanish. We selected 23 articles published between 1985 and 2015. Results: Twenty studies were related to cardiac events and eleven to peripheral vascular events. The most frequent adverse cardiac events were reduced left ventricular ejection fraction, myocardial infarction, changes in the electrocardiogram, heart failure and angina, whereas peripheral vascular events were hypertension and thromboembolism. Conclusion: Oral antineoplastic therapy is associated with different adverse events, including cardiac and peripheral vascular events.